Blood Cell Ratio Combinations for Diagnosing Periprosthetic Joint Infections: A Preliminary Study - Yu Y; Wen Y; Xia J; Dong G; Niu Y (Infection and Drug Resistance)
Yali Yu,1 Yanan Wen,2 Jiaxuan Xia,3 Guixiang Dong,1 Yanli Niu4 1Department of Clinical Laboratory, Zhengzhou Orthopaedic Hospital, Zhengzhou, People’s Republic of China; 2Department of Blood Transfusion, Huaihe Hospital, Henan University, Kaifeng, People’s Republic of China; 3School of Mathematics and Statistic, Henan University, Kaifeng, People’s Republic of China; 4Laboratory of Cell Signal Transduction, Henan Provincial Engineering Centre for Tumor Molecular Medicine, School of Basic Medical Sciences, Henan University, Kaifeng, People’s Republic of ChinaCorrespondence: Yanli Niu, School of Basic Medical Sciences, Henan University, Kaifeng, People’s Republic of China, Email nyl0925@henu.edu.cnBackground: Periprosthetic joint infection (PJI) is a serious complication following total joint arthroplasty (TJA), which requires prompt and accurate diagnosis for effective management. Many biomarkers have been used for PJI diagnosis; however, the identification of the most effective inflammatory biomarker combination for optimal diagnostic accuracy may be poorly reported.Methods: In this prospective, multi-center study, a total of 269 individuals undergoing knee or hip revision arthroplasty were recruited and subsequently categorized based on 2018 ICM PJI criteria into two groups: 93 with periprosthetic joint infection (PJI) and 176 with aseptic failure (AF). Various preoperative biomarkers were analyzed and compared, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), neutrophil-to-lymphocyte ratio (NLR), CRP-to-albumin ratio (CAR), CRP-Albumin-lymphocyte ratio (CALLR), platelet-to-lymphocyte ratio (PLR), platelet-to-albumin ratio (PAR), and neutrophil-to-albumin ratio (NAR). The diagnostic performance of these biomarkers was evaluated using ROC curve analysis and the area under the curve (AUC). Additionally, the Youden index was used to determine optimal threshold values, and positive predictive value (PPV) and negative predictive value (NPV) were calculated to evaluate diagnostic precision.Results: In the PJI group, levels of PAR, CAR, and CALLY were notably higher compared to the AF group, reaching statistical significance (P < 0.05). PAR and CAR were confirmed to have high diagnostic values, with AUC values of 0.779 and 0.718, respectively. CALLY exhibited moderate diagnostic effectiveness, with an AUC of 0.647. When PAR was combined with CRP and ESR, sensitivity and specificity notably improved to 93.8% and 92.5%, respectively. However, subgroup analysis revealed no significant differences in combined inflammatory biomarker levels between the two groups.Conclusion: PAR and CAR prove to be effective combined inflammatory biomarkers for PJI diagnosis, whereas other markers exhibited limited diagnostic utility for PJI.Keywords: prosthetic joint infection, blood cell ratio combinations, PAR, CAR, MSIS